Pengaruh Kompetensi Dan Profesionalisme Terhadap Kinerja Karyawan (Studi Kasus Pada Koperasi Unit Desa Pakis Kabupaten Malang) - Moch Regy Kurniawan; Eka Farida; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
AbstractBased on the research carried out with the aim of knowing and analyzing the effect of competence and professionalism on the performance of the case study employees at the Pakis Village Unit Cooperative. This research belongs to the type of quantitative descriptive research. The method used is multiple linear regression. The sampling technique used a saturated sample, namely all 36 samples of the Pakis Village Unit Cooperative employees. The sampling technique used in this study is saturated sampling where the determination of the sample when all members of the population are used as samples. To solve the problem in this study using SPSS assistance with validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, f test, and t test. From this study, it was found that the competence and professionalism variables had a positive and significant effect simultaneously on employee performance, partially the competence variable had a positive and significant effect on employee performance, while the professionalism variable had a positive and significant effect on employee performance. Keywords: Competence, Professionalism, Employee Performance.